Mapping Solute Clearance From the Mouse Hippocampus Using a 3D Imaging Cryomicrotome - Naessens, Daphne M. P.; Dobbe, Johannes G. G.; de Vos, Judith; VanBavel, Ed; Bakker, Erik N. T. P. (Frontiers in Neuroscience, 2021)
The hippocampus is susceptible to protein aggregation in neurodegenerative diseases such as Alzheimer’s disease. This protein accumulation is partially attributed to an impaired clearance, however, the removal pathways for fluids and waste products are not fully understood. The aim of this study was therefore to map the clearance pathways from the mouse brain. A mixture of two fluorescently labelled tracers with different molecular weights was infused into the hippocampus. A small subset of mice (n = 3) was sacrificed directly after an infusion period of 10 minutes to determine dispersion of the tracer due to the infusion, while another group was sacrificed after spreading of the tracers for an additional 80 minutes (n = 7). Upon sacrifice, mice were frozen and sectioned as a whole by the use of a custom-built automated imaging cryomicrotome. Detailed 3D reconstructions were created to map the tracer spreading. We observed that tracers distributed over the hippocampus and entered adjacent brain structures, such as the cortex and cerebroventricular system. An important clearance pathway was found along the ventral part of the hippocampus and its bordering interpeduncular cistern. From there, tracers left the brain via the subarachnoid spaces in the directions of both the nose and spinal cord. Although both tracers followed the same route, the small tracer distributed further, implying a major role for diffusion in addition to convection. Taken together, these results reveal an important clearance pathway of solutes from the hippocampus.